Strategi Peningkatan Kemampuan Sumber Daya Manusia di Era Digital: Tantangan dan Adaptasi pada Lembaga Pendidikan - Ismunandar, Arif (CV. Kalimasada Group, 2025)
In the ever-evolving digital era, mastery of technology and innovation is key to success, but many human resources (HR) are still lagging behind in digital literacy and innovation skills. This research aims to analyze the challenges faced by human resources and the strategies needed to improve their ability to face the digital era. The method used in this research is library research with a descriptive model, where analysis is carried out on relevant reading sources from existing literature. This descriptive approach allows researchers to understand and analyze the challenges and adaptations of HR in the digital era through detailed interpretation of relevant texts. The results show that human resources have a central position in realizing development performance, with human quality programmed to match the demands of development and society. The existence of the Indonesian nation in the global arena is strongly influenced by the ability of human resources, especially in mastering science and technology. In addition, strategies to improve teachers' abilities, both in pedagogical competence and professionalism, are needed. Therefore, the role of leaders in improving competent human resources, namely those who have adequate knowledge and skills, is very important to adapt to environmental changes.